2019
DOI: 10.1111/anu.12962
|View full text |Cite
|
Sign up to set email alerts
|

Combined or individual effects of dietary magnesium and selenium nanoparticles on growth performance, immunity, blood biochemistry and antioxidant status of Asian seabass ( Lates calcarifer ) reared in freshwater

Abstract: This study was conducted to investigate effects of and interactions between nanoselenium (NanoSe) and nanomagnesium (NanoMg) on growth, humoral immunity, serum biochemistry and antioxidant capacity of juvenile Asian seabass Lates calcarifer reared in freshwater. Four groups of fish with an average weight of 32.78 ± 2.23 g were fed one of the experimental diets for 6 weeks: (a) control (basal diet); (b) NanoSe (basal diet + 4 mg NanoSe/kg diet); (c) NanoMg (basal diet + 500 mg NanoMg/kg diet); and (d) combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 58 publications
(74 reference statements)
4
27
1
Order By: Relevance
“…Yu et al (2020) demonstrated that optimal dietary Nano Se increased antioxidant capacity and resistance to hypoxia stress in grass carp. Moreover, dietary Nano Se (4 mg kg −1 diet) significantly improved antioxidant status and decreased lipid peroxidation in Asian sea bass (Longbaf Dezfouli et al, 2019). Similarly, the highest antioxidant enzyme activities and the lowest MDA levels were observed in common carp fed on 2 mg Nano Se per kg diet (Ashouri et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al (2020) demonstrated that optimal dietary Nano Se increased antioxidant capacity and resistance to hypoxia stress in grass carp. Moreover, dietary Nano Se (4 mg kg −1 diet) significantly improved antioxidant status and decreased lipid peroxidation in Asian sea bass (Longbaf Dezfouli et al, 2019). Similarly, the highest antioxidant enzyme activities and the lowest MDA levels were observed in common carp fed on 2 mg Nano Se per kg diet (Ashouri et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The release of pro-inflammatory cytokines leads to activation of immune cells and production as well as the release of further cytokines (Dawood et al, 2020a,b). Therefore, in the past when the term 'cytokine storm' arose, it explained inflammation as a sudden release of cytokines to upregulate an inflammatory process (Tisoncik et al, 2012 (Zhou et al, 2009;Lee et al, 2009;Khan et al, 2016;Longbaf Dezfouli et al, 2019;Dawood et al, 2019;and Dawood et al, 2020a,b). Kumar et al, (2018) reported that, in P. hypophthalmus exposed to Aeromonas veronii biovar sobria, diet supplementation with Se-NPs (1 mg/kg) induced higher relative % survival and lower cumulative mortality compared with a control diet.…”
Section: Discussionmentioning
confidence: 99%
“…auratus ), olive flounder ( Paralichthys olivaceus ), Asian sea bass ( Lates calcarifer ), red sea bream ( Pagrus major ), Nile tilapia ( O . niloticus ), rainbow trout ( Oncorhynchus mykiss ), rohu ( Labeo rohita ), yellowtail kingfish ( Seriola lalandi ) and Pangasinodon hypophthalmus (Zhou et al, 2009; Lee et al, 2009; Khan et al, 2016; Longbaf Dezfouli et al, 2019; Dawood et al, 2019; and Dawood et al, 2020a,b). Kumar et al, (2018) reported that, in P .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an essential cofactor in glutathione biosynthesis, Mg can inhibit lipid peroxidation by preventing exhaustion of glutathione, which showed similar results as the serum GPx activity in response to low-Mg diets (Zhang et al 2016). In the current study, the activities of SOD, CAT, and GPx were positively correlated with the concentration of Mg. MDA is the final product of lipid peroxidation and an important indicator of membrane injury caused by free radicals (Longbaf Dezfouli et al 2019). Mohammad and Khan (2018) reported that the antioxidant status of Rohu improved with the inclusion of dietary Mg levels up to 460 mg kg −1 diet and then stabilized in groups fed higher levels of Mg, whereas the reverse pattern was observed for the MDA content.…”
Section: Discussionmentioning
confidence: 99%